Variable Methylation of the Epstein-Barr Virus Wp EBNA Gene Promoter in B-Lymphoblastoid Cell Lines - Elliott, Jennifer (American Society for Microbiology, 2004)
During the initial stages of Epstein-Barr virus (EBV) infection of peripheral resting B cells, transcription of the six genes encoding the EBV latency-associated nuclear antigens (EBNAs) is driven from Wp, a promoter that is present in multiple copies within the EBV major internal repeat. As infection progresses, transcription from Wp is downregulated following upregulation of EBNA gene transcription driven from a promoter, Cp, located ca. 3 kb upstream of the first copy of Wp. Recently published data have provided evidence that, concomitant with the switch in EBNA gene promoter usage, Wp becomes heavily methylated (R. J. Tierney et al., J. Virol. 74:10468-10479, 2000). Based on this observation, it has been argued that methylation of Wp plays a pivotal role in suppressing Wp activity in EBV-immortalized B-lymphoblastoid cell lines (LCLs). Here we present data compiled from analyses of Wp methylation in eight randomly selected low-passage-number B-LCLs. These data demonstrate that there is considerable variability in Wp methylation, both between different cell lines and within clonal LCLs. Overall, less methylation of Wp was noted in established, low-passage-number LCLs than was previously observed in bulk cultures of infected B cells at days 18 and 21 postinfection. Importantly, the majority of LCLs examined harbored both unmethylated and methylated copies of Wp. In addition, all low-passage-number LCLs examined contained both Cp- and Wp-initiated EBNA transcripts, arguing for the presence of some transcriptionally active copies of Wp. Taken together, these data argue that other factors, perhaps in conjunction with Wp methylation, play a role in suppressing Wp activity in LCLs.